Towards implementing CLIL (content and language integrated learning) at CBS (Tunja, Colombia) - Mariño, Claudia Marina (Colombian Applied Linguistics Journal, 2014)
Lately, the use of CLIL in classrooms has been expanding due to the interest in educating bilingual children. In Colombia, this approach is becoming known and is being applied in many schools, mainly bilingual. This article presents a case study that sought to investigate how some of the characteristics of a content-based English class can be taken into account to implement CLIL at CBS to contribute to the education offered to these students. The study was supported by the latest theoretical constructs of CLIL from representative authors such as Coyle, Hood, and Marsh (2010), among others. The data consisted of six videotaped classes from fifth grade, a class observation form, a student questionnaire, an informal interview, a teacher’s journal, and other documents such as the teacher’s lesson plans. The results were qualitatively and quantitatively analyzed using Seliger and Shohamy (1990) techniques. The study revealed that the observed classes met several positive standards that can be used when implementing CLIL at the school such as language methodology and assessment. It was also found that specific CLIL characteristics such as the 4Cs and the language components need to be widely understood and worked by teachers and students before implementing CLIL at the school.